Medial canthal defects following tumour excision: To reconstruct or not to reconstruct?. (4th March 2017) - Shafi, Fariha; Rathore, Deepa; Johnson, Andria; Mehta, Purnima; Ahluwalia, Harpreet S.
ABSTRACT: Laissez-faire following excision of peri-ocular tumours has been described, but is not universally well established. We describe our experience with laissez-faire for managing medial canthal defects following tumour excision and compare our outcomes with full thickness skin grafts. Retrospective comparative case series of 68 patients who underwent reconstruction of a medial canthal defect using laissez-faire with sutured Sorbsan (LFS) ( n = 36) or a full thickness skin graft (FTSG) ( n = 32) at the same centre. Tumour diagnosis, defect size, time taken to epithelialise, functional and cosmetic outcomes, complications, follow-up duration and any secondary interventions were recorded. Basal call carcinoma was the most common neoplasm excised (63/68, 93%). Defect size ranged from 7 × 5 mm to 25 × 10 mm. Mean time for wound epithelialisation in LFS group was 33 days. Mean duration of follow-up was 32 months (range 1–80 months) for LFS and 30 months (range 6–60 months) for FTSG. Good functional and cosmetic outcomes were achieved in all 68 patients. Review of clinical photographs showed epicanthic fold in 2 patients and visible scar in 1 patient in the LFS group and 3 cases of hypopigmented scar and 7 hypertrophic scars in the FTSG group. No cases required secondary intervention. There were no cases of postoperative infection. LFS in the medial canthal region is less likely to lead to hypertrophic scarring or cicatricial sequelae compared to FTSG ( p = 0.02). Both techniques are associated with excellent functional and aesthetic outcomes even for larger defects.